Faith and Liberty the Economic Thought of the Late Scholastics. - Chafuen, Alejandro A. (Lanham : Lexington Books, 2003)
Most people think that free-market ideas and theories were first substanially developed in the eighteenth century by figures such as Adam Smith. In this revised edition of Faith and Liberty, Alejandro A. Chafuen illustrates this misconception by examining the sixteenth and seventeenth century writings of a group of Catholic theologians and philosophers, known as the Late-Scholastics. In this revised ediiton, Chafuen blosters his case by including recent and pertinent material which gives rise to new questions and concerns.
12 -- Late-Scholastic Economics Compared with "Classical Liberal" EconomicsPrivate Property; Public Finance; The Theory of Money; Trade; Value and Price; Distributive Justice; Just Wages; Profits; Interest and Banking; Notes; CONCLUSION; INDEX; ABOUT THE AUTHORS.
Description based on print version record.
Keywords: Economics -- History -- To 1800.; Economics -- Moral and ethical aspects; Economics -- Philosophy; Scholasticism -- History; Economics -- History -- To 1800.; Scholasticism -- History; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; Electronic books